Improving the rheological properties and thermal stability of water-based drilling fluid using biogenic silica nanoparticles. (November 2021) - Mirzaasadi, Mojtaba; Zarei, Vahid; Elveny, Marischa; Alizadeh, S.M.; Alizadeh, Vali; Khan, Afrasyab
Abstract: Recent advancement in Nano-based materials in drilling fluid corresponds to improved rheological properties, indicating the proper efficiency of these materials in petroleum industries. To provide a sustainable demand for the formation of drilling fluid by nanomaterials in actual drilling operation, it is essential to control the cost of Nano-based materials. This study aimed to implement a simple synthesis method to produce nanoparticles from an agricultural industry waste named Rice husks (RHs) to eliminate the outrageous expenses of nanomaterials supplementation. Therefore, amorphous silica oxide (SiO2 ) Nanoparticles with two methods (without chemical materials and short; NPS and using chemical treatment; NPT) were synthesized. One of the main reasons to synthesize Nanosilica materials from natural materials was its unique feature in amorphous morphology. Another feature has corresponded to its environmentally friendly properties than the crystalline shape, which belongs to the first group of carcinogens for humans. The nanoparticles characterization was performed by Field Emission Scanning Electron Microscope (FESEM) and X-ray Fluorescence (XRF) apparatus. The results showed that the purity of NPS and NPT were 94.5% and 97.4%, respectively. The utilization of synthesized Nanosilica in the water-based drilling fluid at three concentrations of 3, 5, and 7% w/v was performed at two conditions. The first test is Before Hot Rolling (BHR), which was performed at ambient temperature. The second test is After Hot Rolling (AHR) that was carried out at simulated downhole temperatures of 121.11 and 148.88 °C. The results obtained indicate that all of the rheological properties in samples containing a 3% concentration of NPT were improved compared to NPS. In addition, NPT nanoparticles were able to prevent the thermal degradation of polymers used in drilling fluid. This subject has prevented a sharp drop in rheological properties such as apprentice viscosity and gel strength. Graphical abstract: